Understanding the Links Between Self-Report Emotional Intelligence and Suicide Risk: Does Psychological Distress Mediate This Relationship Across Time and Samples? - Mérida-López, Sergio; Extremera, Natalio; Rey, Lourdes (Frontiers in Psychiatry, 2018)
Abstract Objective: In the last decades, increasing attention has been paid to examining psychological resources that might contribute to our understanding of suicide risk. Although Emotional Intelligence (EI) is one dimension that has been linked with decreased suicidal ideation and behaviors, we detected several gaps in the literature in this area regarding the research designs and samples involved. In this research, we aimed to test a mediator model considering self-report EI, psychological distress and suicide risk across samples adopting both cross-sectional and prospective designs in two independent studies. Method: In Study 1, our purpose was to examine the potential role of psychological distress as a mediator in the relationship between self-report EI and suicide risk in a community sample comprised of 438 adults (270 women; mean age: 33.21 years). In Study 2, we sought to examine the proposed mediator model considering a two-month prospective design in a sample of college students (n = 330 in T1; n = 311 in T2; 264 women; mean age: 22.22 years). Results: In Study 1, we found that psychological distress partially mediated the effect of self-report EI on suicide risk. More interestingly, findings from Study 2 showed that psychological distress fully mediated the relationship between self-report EI and suicide risk at Time 2. Conclusion: These results point out the role of psychological distress as a mediator in the association between self-report EI and suicide risk. These findings suggest an underlying process by which self-report EI may act as a protective factor against suicidal ideation and behaviors. In line with the limitations of our work, plausible avenues for future research and interventions are discussed. Keywords: emotional intelligence, psychological distress, suicide risk, mediator model, prospective design.